(untitled) (Applied Biological Research, 2013)
The present study was aimed to determine the occurrence of Nosema apis (Nosemosis) on Apis mellifera L. in Kashmir. The samples of A. mellifera were collected from 6 districts of Kashmir in 3 seasons viz., spring (March - May), summer (June - August) and autumn (September - November) in the year 2011. The rate of nosemosis infection was assessed by counting the numbers of Nosema spores on the body of bees. Out of 270 honey bee colonies, 49 were infected with Nosema. The highest infection rate was observed in spring (41.1%) and lowest in summer (13.3%), however infection was low in autumn (0%). The mountainous climate of Kashmir and humidity in spring and summer favoured Nosema spreads, whereas Nosema incidence was very low in autumn perhaps due to the lack of humidity.